Temporary Penrose Catheter Fecal Diversion Combined with Negative-Pressure Wound Therapy in Extensive Fournier's Gangrene: A Simple Bridge Before Definitive Stoma Formation. - Ali Levent Işık; Ali Bekraki (Sanatorium Medical Journal, 2026)
Background: Fournier’s gangrene (FG) is a rapidly progressive polymicrobial necrotizing fasciitis of the perineal, perianal, and genital regions associated with high mortality rates. While aggressive surgical debridement and broad-spectrum antibiotics are the cornerstones of treatment, managing severe perianal wounds with extensive abdominal or retroperitoneal spread presents a significant therapeutic challenge. Fecal diversion is often required to prevent wound contamination, but definitive stoma formation can increase patient morbidity. Case Presentation: A 62-year-old obese, diabetic, and hypertensive male presented in septic shock following a blunt abdominal trauma two weeks prior. Computed tomography (CT) revealed extensive gas tracking from the left abdominal wall into the retroperitoneal and pelvic cavities. Urgent surgical debridement confirmed FG originating from a perirectal source. To protect the wound from fecal contamination and facilitate simultaneous negative-pressure wound therapy (NPWT), a low-profile 12 mm silicone Penrose catheter was inserted into the rectum as a temporary, minimally invasive fecal diversion device. Over a 50-day period, the patient underwent serial debridements and NPWT dressing changes. Following the subsequent development of a rectus abdominis abscess and fecal incontinence, a definitive diverting loop ileostomy was performed. The wound successfully granulated, the stoma was reversed at six months, and the patient achieved a favorable recovery. Conclusion: In extensive cases of Fournier’s gangrene tracking into the abdominal wall and retroperitoneum without causing acute peritonitis, combining NPWT with a temporary Penrose catheter fecal diversion system offers a simple, cost-effective, and effective bridging strategy before definitive stoma formation is required.